The Iceberg Decomposition: A Parsimonious Way to Map the Health of Labour Markets - Stijn Baert (Institute of Labor Economics (IZA), 2020)
This article introduces the metaphor of the iceberg in the labour market. While policy in most OECD countries has historically focussed on reducing unemployment (the tip of the iceberg), the group of inactive people (below the waterline) is much larger. Therefore, we point to the clear limitations of the unemployment rate as the (single) key macro-economic indicator of the health of the labour market. A parsimonious dashboard approach utilising the unemployment-to-population ratio and the inactivity-topopulation ratio as two highly appropriate and complementary measures is defended. We show that the ratio of these two indices varies greatly between countries, which calls for different policies for different countries.
Keywords: J64; J08; J23; J24; J68; 330; employment; unemployment; inactivity; labour market policy; labour market indicators